Illness and Identity at the Crossroads: A Cultural Reading of Dur e Aziz Amna’s Novel American Fever - Rafia Kiran Zahid; Muhammad Muneeb Sultan; Zainab Maqsood; Urwa Altaf (`, 2025)
This paper uses postcolonial disability studies to examine how illness and cultural identity are intertwined in Dur e Aziz Amna’s novel American Fever. The story emphasizes the body as a real and symbolic location of negotiation by placing the protagonist’s battle with disease within the larger context of migration and diasporic life. Instead of being presented as a personal suffering, illness is used as a critical lens to reflect on issues of cultural displacement, hybridity, and belonging using Dan Goodley’s concept to analyze intersectionality of disability and postcolonial diasporic fiction. Amna emphasizes how illness undermines established ideas of identity while also allowing for new forms of self-awareness and resistance by setting the protagonist’s physical vulnerability against the background of her experience as an immigrant. This study, which draws on postcolonial disability theory, contends that Amna’s book challenges simplistic depictions of disease as a solely medical condition or a symbol of weakness, therefore complicating traditional illness narratives. Rather, disease turns into a site of contestation where diasporic worries, cultural memory, and affect meet. Thus, the book illustrates how postcolonial bodies bear the dual burden of sickness and displacement while simultaneously providing opportunities to rethink identity outside of the East/West and health/sickness dichotomies. Finally, by showing how embodied fragility can express new forms of agency, belonging, and cultural critique, this paper shows how Amna’s work not only broadens the theoretical scope of postcolonial disability studies but also contributes to the expanding corpus of illness narratives in contemporary fiction. Keywords: Embodied Vulnerability, Diaspora and identity, Rural America, Communal culture, immigrant subjectivity